Contribution of Technical and Vocational Education in Human Resource Development of Urban Areas: A Case of Islamabad City - Dr. Wajiha Kanwal; Dr. Cedric Aimal Edwin; Dr. Abid Ahmad; Madiha Hamid (Journal of Management Practices, Humanities and Social Sciences, 2021)
Education is a basic human right and is considered a key tool for national development. Pakistani society follows the universal pattern of differentiated general education and technical education. One hundred and twenty respondents were selected through a convenient sampling technique and were interviewed by a well-structured research tool (questionnaire). Ten respondents were pretested to check and examine the workability of the questionnaire. Collected data was analyzed through appropriate statistical techniques by using SPSS software, and recommendations were made for the improvement of technical and vocational education regarding human resources. The study found that the majority of the respondents belonged to those skilled persons who were agreed with private organizations taking an interest in conducting vocational training courses. During conducting data, it was also observed that the majority of respondents were agreed that their institutes are providing skills according to international standards. Near to half of the respondents were found a tendency toward getting technical-vocational education in our country with a high ratio. The findings of this study will contribute more in the literature in the area of education in human resource management and will also open a new avenue for practitioners as well as for researchers.